(untitled) (Bangladesh Journal of Neurosurgery, 2019)
Background: Road traffic accident (RTA) is a common problem of neurosurgery department. It is one of the leading causes of death in Bangladesh; the World Health Organization estimated that it kills over 21,000 people in the country annually. Aims: This study aims at to give special attention to RTA patients having head injury or spine injury rather than other injury. Method: The data were collected using a set of structured questionnaires from January/2018 to December/2018. Result: Maximum (93.3%) of RTA patients were managed conservatively and only a few number (6.7%) of patients needed surgery. Recovery was 83% and death was in 17% cases. Conclusion: Head injuries remain the most common and serious type of trauma in RTA and demand good neurosurgical care for such patients. Immediate attention is needed to reduce preventable deaths and morbidities in rural Bangladesh. Bang. J Neurosurgery 2019; 9(1): 22-25